Особливості діяльності мінімузею у закладі вищої освіти - Матвієнко, Світлана Іванівна (My University, 2025)
У статті коротко висвітлено досвід діяльності відкритого у Ніжинському державному університеті імені Миколи Гоголя мінімузею регіональної культури (спеціальність А2 Дошкільна освіта). Презентовано окремі матеріали з Положення про діяльність даного мінімузею, що дозволить ознайомитися з засадами його функціонування. Окреслено деякі заходи щодо вивчення студентами-дошкільниками засад музейної педагогіки, що сприятиме удосконаленню їхньої професійної підготовки.
FEATURES OF THE MINIMUSEUM’S ACTIVITIES IN A HIGHER EDUCATIONAL INSTITUTION The article briefly highlights the experience of the minimuseum of regional culture opened at the Mykola Gogol Nizhyn State University (specialty A2 Preschool Education). Some materials from the Regulations on the activities of this minimuseum are presented, which will allow you to familiarize yourself with the principles of its functioning. Some measures are outlined for studying the principles of museum pedagogy by preschool students, which will contribute to the improvement of their professional training. Keywords: museum, museum center, minimuseum, museum pedagogy, regional culture, higher education institution.
Keywords: музей; музений осередок; міні-музей; музейна педагогіка; регіональна культура; художнє краєзнавство; заклад вищої освіти